UPAYA PEMERINTAH UGANDA DALAM MENGATASI PEMBERONTAK LRA (LORD’S RESISTANCE ARMY) PADA MASA PEMERINTAHAN PRESIDEN YOWERI MUSEVENI (2006-2011) - Al Pusrat "; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The effort by the Government of Uganda to solve the rebel LRA (Lord's Resistance Army) during the reign of President Yoweri Museveni (2006-2011). The conflict between the Government of Uganda and the LRA rebels have caused deaths of more than 24,000 people of Uganda, the Democratic Republic of Congo, the Central African Republic, and Southern Sudan. Finally, the government of Uganda as the origin of the LRA rebels, making policy with military attacks, negotiations, and even some support from the African Union and the United Nations. The concepts used in this research is the National Interest by Donald E. Nuchterlaein and supporting theory used is the Social Movement theory by Stouffer. To solve these problems, the government of Uganda made several efforts including negotiations and ask for the support of the International. In the negotiation process, the government of Uganda entered into an agreement known as the Juba Talks, Uganda is also working with countries that border Southern Sudan, the Democratic Republic of Congo, the Central African Republic as well as international organizations such as the African Union and the United Nations.Key Words: Conflict, Military Operations, Negotiation, Rebels, National Interest.